Are the epigenetic changes predictive of therapeutic efficacy for psychiatric disorders? A translational approach towards novel drug targets - Micale, Vincenzo; Di Bartolomeo, Martina; Di Martino, Serena; Stark, Tibor; Dell'Osso, Bernardo; Drago, Filippo; D'Addario, Claudio (Pharmacology & therapeutics, 2023)
The etiopathogenesis of mental disorders is not fully understood and accumulating evidence support that clinical symptomatology cannot be assigned to a single gene mutation, but it involves several genetic factors. More specifically, a tight association between genes and environmental risk factors, which could be mediated by epigenetic mechanisms, may play a role in the development of mental disorders. Several data suggest that epigenetic modifications such as DNA methylation, post-translational histone modification and interference of microRNA (miRNA) or long non-coding RNA (lncRNA) may modify the severity of the disease and the outcome of the therapy. Indeed, the study of these mechanisms may help to identify patients particularly vulnerable to mental disorders and may have potential utility as biomarkers to facilitate diagnosis and treatment of psychiatric disorders. This article summarizes the most relevant preclinical and human data showing how epigenetic modifications can be central to the therapeutic efficacy of antidepressant and/or antipsychotic agents, as possible predictor of drugs response.
Keywords: MicroRNAs; lidé; mikro RNA; Schizophrenia; antipsychotika; Humans; Antipsychotic Agents; DNA methylation; duševní poruchy; Epigenetics; Antidepressants; epigeneze genetická; Antipsychotics; Epigenesis, Genetic; Depression; Bipolar disorder; DNA Methylation; Mental Disorders; metylace DNA